1997
DOI: 10.21273/jashs.122.6.813
|View full text |Cite
|
Sign up to set email alerts
|

Outcrossing Rate, Yield, and Selective Fruit Abscission in `Ettinger' and `Ardith' Avocado Plots

Abstract: The reciprocal effect of two avocado (Persea americana Mill.) cultivars—Ardith and Ettinger—on outcrossing rate and yield was studied in several orchards in Israel. Multilocus estimates of outcrossing rates were made using the isozyme loci Mdh-1 (malate dehydrogenase) and Aat-1 (aspartate aminotransferase) for `Ettinger' progeny and Lap-2 (leucine aminopeptidase), Pgm-1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 19 publications
6
37
2
Order By: Relevance
“…Although different factors such as temperature [33,34], outcrossing rate [35,36], water and nutrient availability [37] and alternate bearing [29] have been proposed as limiting factors in avocado fruit production, information is still elusive to explain why most flowers prematurely abscise. In avocado, as in other evergreen woody plant species, vegetative and reproductive growth occur simultaneously and, consequently, vegetative and reproductive organs compete for resources provided by either reserve mobilization or photosynthesis [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Although different factors such as temperature [33,34], outcrossing rate [35,36], water and nutrient availability [37] and alternate bearing [29] have been proposed as limiting factors in avocado fruit production, information is still elusive to explain why most flowers prematurely abscise. In avocado, as in other evergreen woody plant species, vegetative and reproductive growth occur simultaneously and, consequently, vegetative and reproductive organs compete for resources provided by either reserve mobilization or photosynthesis [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that successful penetration of the ovary by pollen is time and temperature-dependent and varies among pollen donors (Sedgley and Grant 1983). Abscission of flowers and immature fruits occurs in avocado and selective abscission of immature fruit is reported to have a genetic basis (Degani et al 1986, Degani et al 1997. Two different types of fruit set are described in avocado, Type 1 and Type 2.…”
Section: Linkage Analysismentioning
confidence: 99%
“…Flowering Types A and B complement one another because when one is functionally female (Stage 1), the other is functionally male (Stage 2). DSPD is thought to promote outcrossing between avocado trees of opposite flowering types (Borrone et al, 2008;Degani et al, 1997), but selfing is frequently observed, so factors such as outcrossing rate and the impact of individual pollen donors must also be considered with regard to fruit set and yield. Commercial avocado groves often contain both A and B type cultivars with similar flowering periods.…”
mentioning
confidence: 99%
“…The necessity of interplanting cultivars of opposite flowering type has been much debated among avocado researchers. Using molecular markers, outcrossing has been demonstrated in many studies; however, the rate varies with location, orchard design, developmental stage of the fruit sampled, and the cultivars used as pollen donors Chen et al, 2007;Davenport, 1999;Davenport et al, 1994Davenport et al, , 2007Degani and Gazit, 1984;Degani et al, 1989Degani et al, , 1997Vrecenar-Gadus and Ellstrand, 1985). Borrone et al (2008) used microsatellite markers on Florida avocados and demonstrated that when two complementary cultivars are planted together in almost equal numbers, most of the harvestable fruit result from crosspollination.…”
mentioning
confidence: 99%
See 1 more Smart Citation